2019
DOI: 10.1587/transele.2018ecp5044
|View full text |Cite
|
Sign up to set email alerts
|

A Pulse-Tail-Feedback LC-VCO with 700Hz Flicker Noise Corner and -195dBc FoM

Abstract: This paper proposes a pulse-tail-feedback VCO, in which the tail transistor is driven using pulse-shaped voltage signals with railto-rail swing. The proposed pulse-tail-feedback (PTFB) VCO relies on reducing the current conduction period of the tail transistor and operating the tail transistors in triode region for reducing the flicker and thermal noise from the active elements. Mathematical analysis and circuit level simulations of the phase noise mechanism in the proposed PTFB-VCO is also presented in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Low impedance at the common node may cause the deduction of the phase noise as more noise from the switching operation of the current source affects the VCO core [ 58 ]. The effect on impedance reduction at the common node by DC biasing near the threshold voltage may be minimized as proposed by the previous studies, which include the method of splitting the current source into several transistors, the method of using a source degeneration capacitor, and the method of implementing an additional filter for noise reduction [ 52 , 54 , 58 , 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Low impedance at the common node may cause the deduction of the phase noise as more noise from the switching operation of the current source affects the VCO core [ 58 ]. The effect on impedance reduction at the common node by DC biasing near the threshold voltage may be minimized as proposed by the previous studies, which include the method of splitting the current source into several transistors, the method of using a source degeneration capacitor, and the method of implementing an additional filter for noise reduction [ 52 , 54 , 58 , 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the self-biasing topology implementing adaptive DC biasing using a negative peak detector can compensate for PVT variation and the variation of the Q-factor of the varactor that occurs in tuning the oscillation frequency [ 63 ]. A self-biasing topology with a pulse generator with three different operating states has been proposed to achieve a low conduction angle in steady state and a fast start-up time [ 64 ]. As the main drawback, the auxiliary circuit to implement the adaptive DC biasing requires additional loading to reduce the Q-factor of the LC tank and tuning range and increases the power consumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations